PERAN MANAJER DALAM PENGEMBANGAN WISATA KULINER HALAL DI RUMAH MAKAN BEBEK RIZKY BANGKALAN - Falsafani Arsalan Putra; Raden Mas Mochammad Wispandono (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Halal culinary tourism is extremely needed by Muslim tourists to have safe consumption based on Islamic perspectives. Therefore, it is necessary to have good management from restaurant managers to develop halal aspects so that they can increase customer trust. This study aimed at investigating the role of Bebek Rizky Restaurant Manager at Bangkalan regency in developing halal culinary tourism. The method used in this research was a descriptive qualitative method and employed primary and secondary data. Data collection techniques included observation, interviews, and documentation as primary data, while books, scientific articles, reports, official news, and internet sources as secondary data. This research was built on the managerial role theory literature from Henry Mintzberg (1973) which includes the role of interpersonal roles, informational roles, and decision-making roles. The results of this study indicated that the manager of the Bebek Rizky Bangkalan Restaurant in the development of halal culinary tourism plays an optimal role as Figurehead, Leader, Liaison, Monitor, Disseminator, Spokesperson, disturbance handler, resource allocator, and negotiator. But the entrepreneur role was found to be less optimal.